Lactobacillus gasseri CBT LGA2 alleviates muscle protein degradation and inflammation in immobilization-induced mouse - Jang, Ji Hun; Lim, So Jeong; Choi, Hyo Su; Lim, Sanghyun; Oh, Nam Su (Frontiers in Microbiology, 2026)
IntroductionHindlimb immobilization rapidly induces skeletal muscle atrophy by reducing mechanical loading and accelerating proteolytic activity. This atrophy is further exacerbated by inflammatory signaling, which amplifies FOXO3a-driven expression of Atrogin-1 and MuRF1 and suppresses myogenic capacity. Emerging evidence suggests that specific probiotic strains may counteract these catabolic and inflammatory responses, prompting the evaluation of Lactobacillus gasseri CBT LGA2 (LGA2) in this study.MethodsIn the present study, five probiotic strains were screened in C2C12 myotubes and RAW264.7 macrophages to assess anti-proteolytic and anti-inflammatory activities. Whole-genome sequencing was conducted to determine genetic safety and functional gene profiles. In vivo efficacy was evaluated using a hindlimb immobilization mouse model administered with LGA2 (1 × 10⁸ CFU/kg/day, 3 weeks), followed by assessments of muscle mass, grip strength, fiber morphology, and molecular markers.ResultsLGA2 showed the strongest suppression of dexamethasone-induced muscle protein degradation and lipopolysaccharides-induced inflammatory responses among the screened strains. Genomic analysis identified genes related to antioxidant defense, immune modulation, and muscle protection. In immobilized mice, LGA2 significantly improved grip strength, preserved muscle mass, and restored muscle fiber cross-sectional area. Mechanistically, LGA2 maintained FOXO3a phosphorylation, reduced Atrogin-1 and MuRF1 expression, and recovered myogenin and MyHC isoforms (IIa, IIx, IIb). Additionally, LGA2 lowered TNF-α, IL-6, iNOS, and COX-2 levels while restoring IL-10 in muscle and serum.DiscussionThese findings demonstrate that LGA2 mitigates disuse-induced muscle atrophy through coordinated anti-inflammatory, anti-proteolytic, and pro-myogenic mechanisms. Its genomic safety and multifunctional efficacy support LGA2 as a promising probiotic intervention for muscle health.